Виды и классификация не-факторов при решении задач многокритериальной оптимизации - Михайлова, В. А.; Петров, Э. Г. (ХНУРЭ, 2008)
Different types of uncertainty in multicriterion optimization tasks are considered in the report. Main uncertainty kinds’ classification is made.
Keywords: задача многокритериальной оптимизации